MODEL INTEGRASI KURIKULUM BERBASIS CINTA SEBAGAI UPAYA PENGUATAN MODERASI BERAGAMA DI MADRASAH ALIYAH NEGERI 3 KOTA BANDA ACEH - Aiyub (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2026)
Religious moderation is one of the Indonesian government’s strategic policies for fostering a harmonious society amid religious, cultural, and ethnic diversity. In the context of education, madrasahs play a vital role as institutions that not only impart religious knowledge but also shape students’ character so they can practice Islam in a moderate, inclusive manner that embodies “rahmatan lil ‘alamin” (a blessing for all creation). However, the rise of the digital age has brought new challenges in the form of the increasing spread of narratives of intolerance, extremism, and hate speech through social media, which have the potential to influence the worldview of the younger generation. This situation calls for curricular innovation capable of integrating the values of compassion, humanity, and respect for diversity throughout the entire educational process. One relevant approach is the Love-Based Curriculum, which positions love as the philosophical foundation of learning. This study aims to analyze the integration model of the Love-Based Curriculum in strengthening religious moderation at State Senior High School 3 in Banda Aceh. The study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, documentation, and a review of curriculum documents. Data analysis was conducted using the Miles, Huberman, and Saldaña model through the stages of data condensation, data presentation, and drawing conclusions using source and method triangulation. The results of the study indicate that the values of love are systematically integrated through intracurricular, cocurricular, and extracurricular learning, madrasah culture, religious practices, teacher role modeling, and partnerships with parents. This integration fosters a school culture that values diversity, cultivates tolerance, strengthens national commitment, rejects all forms of violence committed in the name of religion, and accommodates local cultures that align with Islamic values. This study proposes a conceptual model of the Love-Based Curriculum Integration as an innovation in character education that can be replicated in other madrasahs to strengthen the implementation of religious moderation.